Phenylethanolamine-n-methyltransferase inhibition for sustained blood pressure reduction in rats - Abdullah, Aszrin; Mohd Noor, Noriah; Abdul Razak, Tariq (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2015)
Introduction: Hypertension is having an increasing impact on the world population’s morbidity and mortality. The pathogenesis of hypertension is multifactorial but the ‘adrenaline hypothesis’ is being increasingly identified as a cause for hypertension in the young. Objective: The aim of this study is to assess the extent and sustainability of blood pressure fall following peripheral blockade of adrenaline synthesis and to assess the use of THIQ and its ability to block peripheral adrenaline synthesis. ive rats (SHRs) of Wistar-Kyoto Japanese strain rats were obtained and randomised into treated and control groups. Indirect systolic blood pressure (SBP) was measured under ether anaesthesia. 1,2,3,4-Tetrahydroisoquinoline administered chronically. Blood collected for plasma catecholamine measurement and BP/HR measured at regular intervals. Results: Baseline SBP, HR and body weight comparable between treated and control groups (p=1.00, p=0.20 and p=0.22, respectively). Significant SBP drop seen post PNMTI administration (p=0.02). SBP also showed significant drop in week 1 (p=0.03) and week 2 post treatment (p=0.04). Treated SHR plasma catecholamine and dopamine levels also dropped 2-weeks following the PNMTI administration (p= 0.04). Conclusion: This study is consistent with adrenaline hypothesis in the pathogenesis of essential hypertension in young spontaneously hypertensive rats. Consequently, we have also shown that chronic adrenal medullary inhibition with 1,2,3,4-Tetrahydroisoquinoline will result in sustained BP reduction.